Non-communicable diseases in older people living with HIV in four African countries: a cohort study. (March 2022) - Chang, David; Esber, Allahna; Dear, Nicole; Iroezindu, Michael; Bahemana, Emmanuel; Kibuuka, Hannah; Owuoth, John; Maswai, Jonah; Crowell, Trevor; Polyak, Christina; Cavanaugh, Joseph S; Ake, Julie A; et al.
Abstract: Background: The lifespan of people living with HIV is increasing, and non-communicable diseases (NCDs) are becoming an important driver of morbidity in this population. We examined the prevalence of NCDs in older people with HIV and factors associated with development of NCDs. Methods: The African Cohort Study is a prospective cohort enrolling adults with and without HIV at 12 sites in Kenya, Tanzania, Uganda, and Nigeria. Using data collected from Jan 21, 2013 to June 30, 2021, we assessed the prevalence and odds of NCDs, including renal insufficiency (estimated glomerular filtration rate [GFR] <60 mL/min/1·73 m²), elevated blood pressure (any systolic blood pressure >139 mm Hg or diastolic BP >89 mm Hg), obesity (body mass index >30), diabetes (fasting glucose ≥126 mg/dL or receiving medication for diabetes) or hyperglycaemia (fasting glucose ≥99 mg/dL or non-fasting ≥199 mg/dL). Diabetes and hyperglycaemia were collectively evaluated as dysglycaemia. We used multivariable logistic regression with generalised estimating equations to estimate odds ratios (ORs) and 95% confidence intervals (CIs) for factors associated with NCDs. Diabetes and hyperglycaemia models were adjusted for potential confounders including study site and sex. Renal insufficiency models had similar adjustments with the addition of elevated blood pressure and hyperglycaemia. Findings: Of 3434 participants, 2003 (59·3%) were female and 1431 (40·7%) were male, and 2949 (85·9%) were living with HIV. Of people living with HIV, 2188 (74·2%) were younger than 50 years and 761 (25·8%) were aged 50 years or older. Among people living with HIV aged 50 or older, 27·5% (n=209 had elevated blood pressure, 13·4% (102) had dysglycaemia, 4·3% (33) had renal insufficiency, and 11·7% (89) had obesity at last visit. Compared with people without HIV under 50, people living with HIV aged 50 or older had increased adjusted odds of having diabetes (5·29, 95% CI 2·61–10·70), hyperglycaemia (1·86, 1·38–2·50), and renal insufficiency (6·37, 2·38–17·1). We found no differences between individuals aged 50 years or older with and without HIV for diabetes, hyperglycaemia, and renal insufficiency. Interpretation: There was a high burden of NCDs in this cohort. HIV status was not associated with NCD prevalence, although the study was probably underpowered to detect such an association. Screening and treatment for common NCDs, such as raised blood pressure and dysglycaemia, should be considered as part of HIV integrated care. Such an approach might help to prevent other NCDs, such as renal insufficiency, and improve the span of healthy life. Funding: PEPFAR via cooperative agreements between HJF and the US Department of Defense.